Clinical and endoscopic predictors of cytological dysplasia or cancer in a prospective multicentre study of large sessile serrated adenomas/polyps. Issue 3 (2nd March 2015) - Burgess, Nicholas G; Pellise, Maria; Nanda, Kavinderjit S; Hourigan, Luke F; Zanati, Simon A; Brown, Gregor J; Singh, Rajvinder; Williams, Stephen J; Raftopoulos, Spiro C; Ormonde, Donald; Moss, Alan; Byth, Karen; et al.
Abstract : Objective: The serrated neoplasia pathway accounts for up to 30% of all sporadic colorectal cancers (CRCs). Sessile serrated adenomas/polyps (SSA/Ps) with cytological dysplasia (SSA/P-D) are a high-risk serrated CRC precursor with little existing data. We aimed to describe the clinical and endoscopic predictors of SSA/P-D and high grade dysplasia (HGD) or cancer. Design: Prospective multicentre data of SSA/Ps ≥20 mm referred for treatment by endoscopic mucosal resection (September 2008–July 2013) were analysed. Imaging and lesion assessment was standardised. Histological findings were correlated with clinical and endoscopic findings. Results: 268 SSA/Ps were found in 207/1546 patients (13.4%). SSA/P-D comprised 32.4% of SSA/Ps ≥20 mm. Cancer occurred in 3.9%. On multivariable analysis, SSA/P-D was associated with increasing age (OR=1.69 per decade; 95% CI (1.19 to 2.40), p0.004) and increasing lesion size (OR=1.90 per 10 mm; 95% CI (1.30 to 2.78), p0.001), an 'adenomatous' pit pattern (Kudo III, IV or V) (OR=3.98; 95% CI (1.94 to 8.15), p<0.001) and any 0-Is component within a SSA/P (OR=3.10; 95% CI (1.19 to 8.12) p0.021). Conventional type dysplasia was more likely to exhibit an adenomatous pit pattern than serrated dysplasia. HGD or cancer was present in 7.2% and on multivariable analysis, was associated with increasing age (OR=2.0 per decade; 95% CI 1.13 to 3.56) p0.017) and any Paris 0-Is component (OR=10.2; 95% CI 3.18 to 32.4, p<0.001). Conclusions: Simple assessment tools allow endoscopists to predict SSA/P-D or HGD/cancer in SSA/Ps ≥20 mm. Correct prediction is limited by failure to recognise SSA/P-D which may mimic conventional adenoma. Understanding the concept of SSA/P-D and the pitfalls of SSA/P assessment may improve detection, recognition and resection and potentially reduce interval cancer. Trial registration number: NCT01368289.